Current status and future prospects of mesenchymal stem cell therapy for liver fibrosis - Guo, Yang (Zhejiang University Press, 2016)

(untitled) (J Zhejiang Univ Sci B)
Liver fibrosis is the end-stage of many chronic liver diseases and is a significant health threat. The only effective therapy is liver transplantation, which still has many problems, including the lack of donor sources, immunological rejection, and high surgery costs, among others. However, the use of cell therapy is becoming more prevalent, and mesenchymal stem cells (MSCs) seem to be a promising cell type for the treatment of liver fibrosis. MSCs have multiple differentiation abilities, allowing them to migrate directly into injured tissue and differentiate into hepatocyte-like cells. Additionally, MSCs can release various growth factors and cytokines to increase hepatocyte regeneration, regress liver fibrosis, and regulate inflammation and immune responses. In this review, we summarize the current uses of MSC therapies for liver fibrosis and suggest potential future applications.